Mesua beccariana (Clusiaceae), a source of potential anti-cancer lead compounds in drug discovery - Teh, Soek Sin; Ee, Gwendoline Cheng Lian; Mah, Siau Hui; Lim, Yang Mooi; Rahmani, Mawardi (MDPI, 2012)
An investigation on biologically active secondary metabolites from the stem bark of Mesua beccariana was carried out. A new cyclodione, mesuadione (1), along with several known constituents which are beccamarin (2), 2,5-dihydroxy-1,3,4-trimethoxy anthraquinone (3), 4-methoxy-1,3,5-trihydroxyanthraquinone (4), betulinic acid (5) and stigmasterol (6) were obtained from this ongoing research. Structures of these compounds were elucidated by extensive spectroscopic methods, including 1D and 2D-NMR, GC-MS, IR and UV techniques. Preliminary tests of the in vitro cytotoxic activities of all the isolated metabolites against a panel of human cancer cell lines Raji (lymphoma), SNU-1 (gastric carcinoma), K562 (erythroleukemia cells), LS-174T (colorectal adenocarcinoma), HeLa (cervical cells), SK-MEL-28 (malignant melanoma cells), NCI-H23 (lung adenocarcinoma), IMR-32 (neuroblastoma) and Hep-G2 (hepatocellular liver carcinoma) were carried out using an MTT assay. Mesuadione (1), beccamarin (2), betulinic acid (5) and stigmasterol (6) displayed strong inhibition of Raji cell proliferation, while the proliferation rate of SK-MEL-28 and HeLa were strongly inhibited by stigmasterol (6) and beccamarin (2), indicating these secondary metabolites could be anti-cancer lead compounds in drug discovery.